EVALUASI PROGRAM REVITALISASI PASAR MARIHAT BANDAR DI KABUPATEN SIMALUNGUN (Evaluation of the Marihat Bandar Market Revitalization Program in Simalungun Regency) - Sinta Nababan; Theodora M. Katiandagho; Oktavianus Porajouw (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The objective of this research is to evaluate the revitalization program in Marihat Bandar Market in terms of comfort, cleanliness, order and environmental friendliness. A program can be said to be successful if the results of the implementation of the program are in accordance with the set plans and objectives. Not only increasing competitiveness, revitalization is also able to empower traditional markets so as to create a comfortable, clean, orderly and environmentally friendly market atmosphere. One of the traditional markets that is the target of the traditional market revitalization program of the Simalungun Regency Government of North Sumatra Province is the Marihat Bandar Market. The government took the revitalization policy starting in July 2019 and finished in November 2019 and traders began to actively trade again in early March 2020. This study uses a Likert scale as a measurement technique for the variables to be measured. The researchÂ  results showed that the Marihat Bandar Market revitalization program in terms of comfort, cleanliness, order and environmental friendliness in general is classified as good with the assessment of traders and buyers of 68.5%.